2016
DOI: 10.1039/c6ra23059h
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification and porosimetry of vertically aligned hexagonal mesoporous silica films

Abstract: Grafting vertically aligned mesoporous silica films with small organosilane precursors increases pore hydrophobicity, whereas larger reagents change only the film surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(97 reference statements)
0
9
0
Order By: Relevance
“… 39 , 40 Highly polar solvents such as water are likely to produce large hysteresis because of interaction with the hydroxyl groups on the pore wall during the adsorption–desorption process. 41 Changes in refractive index values were measured during the experiment, which allowed for the volume fraction of toluene present within the pores to be calculated using the Lorentz–Lorenz effective medium approximation. 39 …”
Section: Resultsmentioning
confidence: 99%
“… 39 , 40 Highly polar solvents such as water are likely to produce large hysteresis because of interaction with the hydroxyl groups on the pore wall during the adsorption–desorption process. 41 Changes in refractive index values were measured during the experiment, which allowed for the volume fraction of toluene present within the pores to be calculated using the Lorentz–Lorenz effective medium approximation. 39 …”
Section: Resultsmentioning
confidence: 99%
“…We have shown that the silica films contain pores which are aligned nearly perpendicular to the film without significant interconnection using TEM . We have characterized the films using ellipsometric porosimetry demonstrating a high pore accessibility (measured porosity 38%) and determined the pore diameter to be 1.4 nm which is within error the same as the pore diameter determined from STEM images . These films were further optimized to reduce defects at a range of scales to ensure that the largest possible fraction of the finished electrodes is only accessible via the ≈1.5 nm pores (see the SI).…”
mentioning
confidence: 87%
“…13 We have characterized the films using ellipsometric porosimetry demonstrating a high pore accessibility (measured porosity 38%) and determined the pore diameter to be 1.4 nm which is within error the same as the pore diameter determined from STEM images. 14 These films were further optimized to reduce defects at a range of scales to ensure that the largest possible fraction of the finished electrodes is only accessible via the ≈1.5 nm pores (see the SI). We estimate, using a combination of SEM and TEM imaging, that more than 95% of the electrode is covered by mesoporous silica with ≈1.5 nm pores.…”
mentioning
confidence: 99%
“…This procedure can be done in a variety of ways but in the specific example cited here, electrochemical methods were used. [5] This system concerns pore alignment in 2D hexagonal mesoporous thin Table 1. S stands for Surfactant, I stands for inorganic species, X stands for mediating ions, After.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%